Whether Service Quality, Price and Location Can Increase Purchasing Decisions for Mobile Phones and Accecories - Desy Yanti Anggreni; Sri Sarbini; Wahyoe Herlyana Dewi; Karjono Karjono; Samsul Hadi; Nurul Qomariah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The need for smartphones and their accessories is currently increasing significantly with the community's need for smartphones and accessories. This study aims to determine and analyze the effect of service quality, price and location on purchasing decisions for mobile phones and accecories at